2005
DOI: 10.1016/j.jse.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and interobserver reliability for the strength test in the Constant-Murley shoulder assessment

Abstract: This study evaluates the standardised strength test in the Constant-Murley-shoulder assessment on shoulder-healthy adults in a randomised, single-blind design. The following questions were to be answered; 1) can the spring-balance and a digital dynamometer both yield the same result 2) intra-and inter-observer reliability of the strength test 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 22 publications
0
52
0
2
Order By: Relevance
“…The CMS is reported to be reliable and valid in patients with shoulderor rotator-cuff-related pathologies. 21,32,33 …”
Section: American Shoulder and Elbow Surgeons Questionnaire (Ases) 11mentioning
confidence: 99%
“…The CMS is reported to be reliable and valid in patients with shoulderor rotator-cuff-related pathologies. 21,32,33 …”
Section: American Shoulder and Elbow Surgeons Questionnaire (Ases) 11mentioning
confidence: 99%
“…The limit of the manual resistance was reported to be from 220 to 294.2 N (30 kg) in previous studies [1][2][3][4][5][6] . Methods previously reported for fixing a HHD to overcome this problem and prevent the angle of the joint from changing include using a stick 7) , a steel support 8) , and a belt [9][10][11][12][13][14][15] . Among these studies, Katoh et al 12,13) used a belt to help steady the HDD and investigated the reliability of isometric muscle strength measurements of the lower limbs (flexion, extension, abduction, adduction, internal rotation and external rotation of the hip, flexion and extension of the knee, and dorsiflexion and plantar flexion of the ankle), in healthy men and women with a mean age of 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…The scoring system has been demonstrated to have high rates of intraobserver and interobserver correlation and to correlate strongly with patient satisfaction. (10) In our study which evaluated 50 patients undergoing double-row repair of rotator cuff tear (>3 cm), we found that there was an improvement in the constant score from 43.68 to 76.52 and from 44.36 to 77 in both the groups respectively (Refer chart 1 under 'Results and observations' ) after a mean followup of 24 months. But, between the two groups, our study didn't find any significant difference in the final clinical outcome.…”
Section: Discussionmentioning
confidence: 72%